Genetic Diversity of Human Rotavirus A Among Hospitalized Children Under-5 Years in Lebanon - Harastani, Houda H.; Reslan, Lina; Sabra, Ahmad; Ali, Zainab; Hammadi, Moza; Ghanem, Soha; Hajar, Farah; Matar, Ghassan M.; Dbaibo, Ghassan S.; Zaraket, Hassan (Frontiers in Immunology, 2020)
Human rotavirus remains a major cause of gastroenteritis worldwide despite the availability of effective vaccines. In this study, we investigated the genetic diversity of rotaviruses circulating in Lebanon. We genetically characterized the VP4 and VP7 genes encoding the outer capsid proteins of 132 rotavirus-associated gastroenteritis specimens, previously identified in hospitalized children (<5 years) from 2011 to 2013 in Lebanon. These included 43 vaccine-breakthrough specimens and the remainder were from non-vaccinated subjects. Phylogenetic analysis of VP4 and VP7 genes revealed distinct clustering compared to the vaccine strains, and several substitutions were identified in the antigenic epitopes of Lebanese specimens. No unique changes were identified in the breakthrough specimens compared to non-breakthroughs that could explain the occurrence of infection in vaccinated children. Further, we report the emergence of a rare P[8] OP354-like strain with a G9 VP7 in Lebanon, possessing high genetic variability in their VP4 compared to vaccine strains. Therefore, human rotavirus strains circulating in Lebanon and globally have accumulated numerous antigenic changes compared to those currently used in the licensed vaccines. The successful spread and continued drifting of these strains over time might undermine the effectiveness of the vaccines. The effect of such antigenic changes on vaccine efficacy remains to be assessed.